Effect of Physical Exertion in Some of Antioxidant concentrations for Young Player's in Handball - Ahmed Kadhim Abdulkareem (Journal of Global Pharma Technology, 2016)
The study aimed to identify the effect of physical effort in some concentrations of antioxidants for young handball players. The study also revealed that there are statistically significant differences in physical exertion in some antioxidant concentrations of young handball players. It has been shown that the importance of research helps to detect the degrees of emotional arousal and knowledge of its relationship with antioxidants that work to get rid of the free radicals causing fatigue for young basketball players. The researchers used the training curriculum to suit the nature of the problem on the players of Kufa Sports Club youth handball for the season (2017-2018) and the number of (12) players, was adopted method of comprehensive inventory in the selection of the sample were identified two players for the purpose of conducting the pilot, The main sample is (10) players. After the tests of pretest and posttest, data were collected and processed statistically to obtain the results through which reached the most important conclusions, the physical effort at the heart rate 180 beat/second was affected by the antioxidants taken by the researcher and the component of Selenium (Se) and (Vitamin E And C) was the result of good preparation and systematic training of young handball players. The rate of change of vitamin(C) was higher than that of vitamin (E) and the lower selenium was achieved after the physical exertion at 180 beat/second for youth players in handball.Keywords: Physical exertion, Antioxidants and handball.